The effects of the recent economic crisis on social protection and labour market arrangements across socio-economic groups - Gaetano Basso; Matthias Dolls; Werner Eichhorst; Thomas Leoni; Andreas Peichl (Institute for the Study of Labor (IZA), 2011)
The Great Recession did not only affect European countries to a varying extent, its impact on national labour markets and on specific socio-economic groups in those markets also varied greatly. Institutional arrangements such as employment protection, unemployment insurance benefits and minimum income support, working time flexibility and wage setting played a crucial role in determining to what extent the economic crisis led to higher unemployment, wage cuts or income losses and rising poverty. As the crisis gained momentum, the action of automatic stabilisation mechanisms built into the national tax-benefit and social protection systems was accompanied by heterogeneous sets of discretionary policy measures. While these factors can explain cross-country variation in labour market developments, they also lead to an unequal distribution of economic risks associated with the crisis across socio-economic groups. The present paper aims to investigate and assess to what extent the financial and economic crisis that hit the global economy in 2008-2009 impacted these labour market developments and to what extent different socio-economic groups were affected.
urn:nbn:de:101:1-201111212962
Keywords: H24; J65; J68; 330; automatic stabilisers; unemployment protection; tax systems; Europe; Great Recession; Wirtschaftskrise; Arbeitslosigkeit; Armut; Soziale Gruppe; Arbeitslosenversicherung; Arbeitnehmerschutz; Eingebauter Stabilisator; Europa; Finanzmarktkrise; Welt